2015
DOI: 10.1128/jb.02185-14
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Aromatic β-Glucoside Utilization by Successive Mutational Steps in Escherichia coli

Abstract: The bglA gene of Escherichia coli encodes phospho-␤-glucosidase A capable of hydrolyzing the plant-derived aromatic ␤-glucoside arbutin. We report that the sequential accumulation of mutations in bglA can confer the ability to hydrolyze the related aromatic ␤-glucosides esculin and salicin in two steps. In the first step, esculin hydrolysis is achieved through the acquisition of a four-nucleotide insertion within the promoter of the bglA gene, resulting in enhanced steady-state levels of the bglA transcript. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…The absence of this ABC transporter in Tatumella and the concomitant antibiotic resistance may increase ecological competitiveness of species exposed to these compounds (Hacker and Carniel, 2001 ). Ecological advantages are likely also obtained from some of the predicted PTSs, which have previously been linked to enhanced recycling of cell wall components under nutrient-poor conditions (e.g., PTSs involving N-acetylmuramic acid and N-acetylglucosamine; Jaeger and Mayer, 2008 ), and the uptake of plant-derived carbon compounds (e.g., PTS involving arbutin and salicin; Zangoui et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The absence of this ABC transporter in Tatumella and the concomitant antibiotic resistance may increase ecological competitiveness of species exposed to these compounds (Hacker and Carniel, 2001 ). Ecological advantages are likely also obtained from some of the predicted PTSs, which have previously been linked to enhanced recycling of cell wall components under nutrient-poor conditions (e.g., PTSs involving N-acetylmuramic acid and N-acetylglucosamine; Jaeger and Mayer, 2008 ), and the uptake of plant-derived carbon compounds (e.g., PTS involving arbutin and salicin; Zangoui et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…4c). It has been reported that E. coli used the aromatic beta-glucosidases (arbutin, salicin, and esculin) as the carbon source [43]. These results suggested that adding glycerol could avoid the degradation of C-glycosyl avonols by probably suppressing catabolic systems for utilization of the aromatic beta-glucosidases.…”
Section: Effects Of Glycerol On Avoiding Degradation Of C-glycosyl Av...mentioning
confidence: 96%
“…These sugars included monosaccharides (L-enantiomers of arabinose and rhamnose and D-enantiomers of ribose, xylose, galactose, glucose, fructose and mannose), disaccharides (D-enantiomers of cellobiose, maltose, lactose, melibiose, saccharose/sucrose and trehalose and gentiobiose), glycosides (amygdalin, arbutin, esculin and salicin), polysaccharides (D-raffinose), polyols (glycerol, galacticol, inositol, and D-mannitol), and salts (potassium gluconate). Isolate JZ38 has the genomic potential for the metabolism of arabinose (araBAD) (Fritz et al, 2014), arabinogalactan (bgaB/ganA, ganB) (Watzlawick et al, 2016), cellulose and cellobiose (bcsZ, two copies of bglX, bglB, yliI) (Xie et al, 2007), citric acid (citABCDEFXG, citA in plasmid p2) (Martín et al, 2004), galactose (lacA, galK, galT) (Chai et al, 2012), galacticol (gatD, gatYZ, gatR) (Nolle et al, 2017), glucose (pgm, yihX, glk, pgi), glycerol (glpK, glpD) (Holmberg et al, 1990;Yang et al, 2014), glycosides (bglB, bglA/ascB, ascG) (Desai et al, 2010;Zangoui et al, 2015), inositol (iolBCDEGHI) (Morinaga et al, 2010), lactose (lacA, lacZ) (Zeng et al, 2010), maltose/matlodextrin (malP, malQ, malS, malZ, glvA) (Boos and Shuman, 1998), mannitol (mtlD) (Wisselink et al, 2004), melibiose and raffinose (rafA, rafR, scrB) (Russell et al, 1992; Hugouvieux-Cotte-Pattat and Charaoui-Boukerzaza, 2009), rhamnose (rhaBAD) (Schwartz et al, 1974;Rodionova et al, 2013), ribose (rbsK, rbsD, rbsR) (Mauzy and Hermodson, 1992;Sigrell et al, 1998), sucrose (scrB, two copies of scrK, scrR) (Hugouvieux-Cotte-Pattat and Charaoui-Boukerzaza, 2009), trehalose (two copies of treA, treC, treR) (Baker et al, 2018), and xylose (xylAB) (Shamanna and Sanderson, 1979).…”
Section: Jz38-plant Interactionmentioning
confidence: 99%